Pengaruh Kebijakan Penerapan Electronic Government terhadap Peningkatan Kualitas Pelayanan pada Puskesmas di Kota Madiun - Nurul Ni'matul Usriyah; Tukiman Tukiman (J-MAS (Jurnal Manajemen dan Sains), 2022)
The application of electronic government is an effort by the government to adopt information technology to improve the quality of public services. However, the implementation of electronic government in its implementation still has problems in it. This study aims to determine the effect of the implementation of electronic government policies on improving the quality of services at the Puskesmas in Madiun City. The research method used in this research is quantitative with questionnaires to answer the research problem formulation. The population in this study were users of health services at health centers throughout Madiun City who used electronic government (Sist Bro) services at Puskesmas in the Puskesmas environment in Madiun City as many as 130 people from six Puskesmas in Madiun City where the sample was 57 people whose answers were analyzed using SPSS. The results of the analysis state that the variable of the implementation of electronic government has a significant and positive effect on service quality.